Homozygous HPS1 variant in an Iranian sibling pair with Hermansky–Pudlak syndrome - Ensiyeh Bahadoran; Mehrzad Ramezani; Sahar Moghbelinejad (Egyptian Journal of Medical Human Genetics)
Abstract Background Hermansky–Pudlak syndrome (HPS) is an uncommon autosomal recessive disease that presents with bleeding diathesis and oculocutaneous albinism (OCA). Mutations in genes related to the synthesis of organelles connected to lysosomes cause this disease. Herein, we report a case of an Iranian sibling pair with a mutation in the HPS1 gene. Case presentation A 26-year-old woman and her 24-year-old brother, both born to consanguineous parents, presented with OCA, nystagmus, and a history of easy bruising. Whole-exome sequencing identified a homozygous missense mutation (c.1754T > C, p.Leu585Pro) in the HPS1 gene. Segregation analysis confirmed that the parents were heterozygous carriers of this mutation. The clinical presentation and genetic findings supported the diagnosis of HPS-1. Conclusion Identification of the c.1754T > C (p.Leu585Pro) mutation in HPS1 in this family expands the genetic understanding of HPS. This case highlights the utility of next-generation sequencing in identifying novel genetic variants, which can aid in the diagnosis and management of rare syndromes such as HPS. Further functional studies are necessary to elucidate the implications of this mutation in disease pathogenesis.